2017
DOI: 10.1016/j.tecto.2017.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Is the Okavango Delta the terminus of the East African Rift System? Towards a new geodynamic model: Geodetic study and geophysical review

Abstract: The Okavango Graben (OG) has been considered as the terminus of the southwestern branch of the East African Rift System (EARS) since the 1970's based on fault morphology and early seismic and geophysical data. Thus it is assumed to be an incipient rifting zone, analogous to the early stage of mature rifts in the EARS. Recent geodetic data and geophysical studies in the area bring new insights on the local crust and lithosphere, mantle activity and fault activity. In this study, we computed the velocities for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 47 publications
0
42
1
Order By: Relevance
“…The white polygon marks the Makgadikgadi-Okavango-Zambezi Basin (MOZB) following the definition of Ringrose et al (2008). The extent the of underlying cratons that bound the MOZB basin are after Pastier et al (2017) and Yu et al (2017) where the Kalahari Craton is consists of the agglomerated Kaapvaal and Zimbabwe cratons. Inset: The white area denotes the Kalahari Basin on the African continent.…”
Section: Structurementioning
confidence: 99%
See 2 more Smart Citations
“…The white polygon marks the Makgadikgadi-Okavango-Zambezi Basin (MOZB) following the definition of Ringrose et al (2008). The extent the of underlying cratons that bound the MOZB basin are after Pastier et al (2017) and Yu et al (2017) where the Kalahari Craton is consists of the agglomerated Kaapvaal and Zimbabwe cratons. Inset: The white area denotes the Kalahari Basin on the African continent.…”
Section: Structurementioning
confidence: 99%
“…The basin is situated between elevated structural arches (Gumbricht, McCarthy, & Merry, 2001) overlying Proterozoic and Mesozoic rift structures (Dixey, 1956; Doucouré & de Wit, 2003; Modisi, Atekwana, Kampunzu, & Ngwisanyi, 2000; Reeves & Hutchins, 1982; Smith, 1984). Recent seismic, tomographic, and magnetotellurics studies suggest that lithospheric stretching is the result of inter‐cratonic differential tectonic strains of the surrounding Archean cratons (i.e., Congo and Kalahari cratons, Figure 1a; Pastier, Dauteuil, Murray‐hudson, & Moreau, 2017; Yu et al., 2017), where the upper mantle is rheologically weak (Moorkamp, Fishwick, Walker, Jones, & Mt, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although southern Africa experiences diffuse, low‐magnitude seismicity (e.g., Pastier et al, ), no active structure has been identified in the epicentral region of the Botswana earthquake. The nearest active faults are 350 km to the north bounding the isolated Okavango tectonic basin, where a M6.7 earthquake occurred in 1952 (Modisi et al, ; Reeves, ).…”
Section: Introductionmentioning
confidence: 99%
“…The nearest active faults are 350 km to the north bounding the isolated Okavango tectonic basin, where a M6.7 earthquake occurred in 1952 (Modisi et al, ; Reeves, ). This basin has been interpreted by some as an incipient rift at the western end of a belt of weak seismicity that extends from the Okavango basin through the Kariba graben to the east and connects to the Rukwa region of the East African Rift (Modisi et al, ; Scholz et al, ), although that interpretation has recently been challenged (Pastier et al, ). The 2017 Bostwana earthquake is located well away from these structures.…”
Section: Introductionmentioning
confidence: 99%